Analysis of the synthesis of 1,1-dibutoxyethane in a simulated moving-bed adsorptive reactor - Graça, Nuno S. (2014)
The synthesis of 1,1-dibutoxyethane was carried out in a simulated moving-bed pilot unit LICOSEP 12-26 (Novasep, France) with 12 columns packed with the commercial ion-exchange resin Amberlyst 15(Rohm & Haas, France). Experimentally the best raffinate purity obtained was 85% with a productivity of 5.04 kg L−1 d−1 and a desorbent consumption of 13.5 L kg−1. The TMBR model was used to construct reaction/separation regions and to study the influence of feed composition, switching time, flow rates and mass-transfer resistances on the SMBR performance. The SMBR process shows a potential to be a competitive, efficient and environmentally friendly way to produce 1,1-dibutoxyethane and other acetals.